Multifunctional Polymer Composites for Automatable Induction Heating with Subsequent Temperature Verification - Reichstein, Jakob; Raczka, Theodor; Stauch, Claudia; Schug, Benedikt; Müssig, Stephan; Mandel, Karl (Advanced Engineering Materials, 2024)
Manipulating ferromagnetic particles using an alternating current (AC) magnetic field is a versatile method for quick, local, and on-demand heat generation. These particles can be incorporated into various matrices as heating elements. Their heat release can be controlled by adjusting process or material parameters. Herein, a proof-of-concept for a flexible polymer composite with customizable magnetically triggered heat release due to prior object identification via fluorescence readout is presented. The maximum temperature resulting from this process can be determined through a second fluorescence readout ex post. This novel combination of functionalities results from the synergistic interaction of inductively heatable magnetic supraparticles (SPs) and luminescent communicating SPs in one polydimethylsiloxane composite. The surface of the composite can be heated to the maximum temperatures of choice in a range between 125 and 200 °C within 2 s. Heat release and temperature verification provide spatial resolution of millimeters. The identification signature and the working range of the temperature indication functionality of the composite are customizable by exploiting its modular material design. The temperature indication functionality of the composite offers spatial resolution and ex-post readout at any point of interest, making it a versatile alternative to established optical thermometry methods.<br
Keywords: supraparticles; magnetic nanoparticle; induction heating; temperature indicators; smart additives